The Effect of the Blood Cupping Therapy on High Density Lipoprotein (HDL) and Low Density Lipoprotein (LDL) in Hypercholesterol Patients - Wahyudi Widada1 , Teddy Ontoseno2 , Bambang Purwanto3 , Suhartati4 , Imam Subadi5 , Hari Basuki Noto (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Hypercholesterol is a high cholesterol level in the blood. Blood cupping therapy is a techniqueof excreting metabolic waste in the blood through the skin. The study aimed to measure any effect of bloodcupping therapy to HDL and LDL cholesterol. Method: It was a Quasi-Experimental study using humansas research subjects. Non random consecutive sampling. Patiens with hypercholesterol after 12 hours offasting were treated with blood cupping, 9 points. Research subjects were 51 men divided into three groups,the cupping group only consisted of 17 men, the drug group without cupping consisted of 17 men, andthe cupping and drug consisted 17 men. Collecting data from third of the groups as pre and post data.The data were analyzed by Mann Whitney, Wilcoxon and Kruskal Wallis. The research took place at theLaboratory of Biochemistry, Universitas Jember. Results: Measurement of HDL cholesterol on the cuppinggroup was pretest=33.03±3.73; posttest=37.58±6.54; p=0.000. The drug group was pretest=33.40±3.18;posttest=33.56±3.50; p=0.788. The cupping and drug group was pretest=34.32±3.38; posttest=37.61±2.01;p=0.002. Kruskal Wallis test on pretest group was 0.534 and on posttest group was 0.002. Measurement ofLDL cholesterol on the cupping group was pretest=154.70±39.68; posttest=123.89±41.86; p=0.000. Thedrug group was pretest=151.24±44.17; posttest=151.24±44.17; p=0.019. The cupping and drug group waspretest=147.48±62.66; posttest=105.57±57.94; p=0.001. Kruskal Wallis test on pretest group was 0.439and on posttest group was 0.082. This means that there was no difference in the average pretest and posttestLDL levels in the cupping, drug, cupping and drug groups. Conclusion: The intervention of blood cuppingtherapy can increase HDL cholesterol level, and reduce LDL cholesterol level. Further research needs to bedone to measure the potential prevention of atherosclerosis.